ANALISIS FAKTOR PENENTU NIAT PEMBELIAN MOBIL LISTRIK DI KALANGAN GENERASI Z (GEN Z) DI KOTA BATAM - Ang, Nicky Jefferson; Fahlevi, Renza; Qadri, Rizni Aulia (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the influence of perceived benefits, perceived risks, and social influences on attitudes, as well as the influence of attitudes on purchase intentions in the context of electric car purchasing behavior among Generation Z (Gen Z) in Batam City. The research approach was quantitative. Data were obtained by distributing questionnaires to 190 respondents aged 17–28 years who resided in Batam and were interested in purchasing an electric car. The collected data were analyzed using Partial Least Squares (PLS)-based Structural Equation Modeling. The results showed that perceived benefits did not significantly influence attitudes, indicating that the cost efficiency and functional benefits of electric cars have not yet been able to shape positive attitudes among Gen Z. Conversely, perceived risks and social influences did not significantly influence attitudes. This illustrates that perceptions and social risk incentives play a significant role in shaping the attitudes of young consumers. Furthermore, attitudes were shown to have a significant positive effect on electric car purchase intentions, indicating that positive attitudes are one of the driving factors driving electric car purchase interest among Gen Z Batam. These findings provide theoretical contributions to understanding electric vehicle adoption behavior among the younger generation and practical contributions to automotive companies in designing more effective marketing strategies for the Gen Z market.